An Analysis of Lecturers' Perception toward the Interactive E-book used in Advanced Grammar at English Department of Universitas Negeri Padang - Muflihatuz Zakiyah; Fitrawati Fitrawati (Journal of English Language Teaching, 2020)
That English becomes the most preferred language to use in this digital era and the demand of the availability of various books (textbook, journal, and e-book, etc.) in order to fulfil one of requirements to become a world class university inspired some grammar lecturers in English Department of UNP to develop an interactive grammar e-book.  In order to find out whether the interactive grammar e-book was designed according to the criteria and the users’ needs, the feedback from grammar lecturers on the e-book are demanded. This study aimed to find out the lecturers’ perception on interface, interactivity, content materials and exercises, as well as practicality of the interactive grammar e-book. This survey study involved six grammar lecturers at English Department who were chosen selectively. Questionnaire containing 70 items and followed by four scales was distributed to the lecturers. The data were analyzed by finding the mean scores for each item. Then, the mean scores were converted into degree of perception. It is found that lecturers have positive perceptions on the five aspects. However, there are some suggestions given by them who gave negative response on questionnaire. Thus, there is a little improvement needed on the e-book according to the lecturers’ perception.